Energy Dispersive X-ray Fluorescence Analysis Imaging—Development and Applications - Carvalho, Patrícia Miguel da Silva (2022)
The Energy Dispersive X-ray Fluorescence (EDXRF) analysis technique presents unique features for elemental content evaluation of varied samples, such as its non-destructive nature, high sensitivity, or reduced costs. Many EDXRF studies have been focused on the determination of elemental concentration variations between normal and tumour tissues, to compare and correlate findings with factors such as the type and the stage of tumours, or the patients’ age and sex. Mapping elemental distributions may also provide insightful information on these types of samples, namely the identification of regions of elemental accumulation or depletion, and the demarcation of tumour margins, thus contributing to the unbiased differentiation between normal and abnormal tissues. The main goals of this work are to quantitatively determine the elemental content in paired samples of normal and tumour human tissues, and to map the corresponding elemental distributions. An improved methodology for the quantitative analysis of biological tissues is introduced, to surpass existing limitations (e.g., reduced number of tissue samples) that have lead to low-accuracy quantifications and statistically irrelevant conclusions. Moreover, a Full-field Energy Dispersive X-ray Fluorescence (FF-XRF) imaging spectrometer based on the 2D Thick-COBRA (2D-THCOBRA) micropattern gas detector is presented as a novel, cost-effective tool of simple instrumentation, for detection and mapping of elements in biological tissues. Different sample sets of normal and tumour human tissues were analysed, and it was possible to quantify concentration variations of light (e.g., K) and heavy elements (e.g., Fe and Zn). However, the contribution of these results to cancer studies is minimal due to the reduced number of analysed samples. To overcome this limitation, mirror samples of "fresh" and paraffin embedded tissues were analysed, and it was verified that the embedding process alters the elemental content of tissues. As such, the monitoring of the elemental content of tissues throughout the process is suggested. The FF-XRF imaging spectrometer based on the 2D-THCOBRA detector was used to map paired samples of normal and tumour human tissues. Elements present in small amounts (a few μg/g) were detected and the corresponding distributions were mapped. Overall, the detected elements are evenly distributed on the samples’ surface, with the exception of Ca in the lung tumour tissue. Throughout the analysed sample, calcium deposits, a possible malignancy indicator, were identified. The imaging spectrometer was also applied in the study of Zebrafish exposed to Mn, Se, and Pb. Heavy metal accumulation in the intestinal region was identified in all the analysed fish. Despite the suitability of the system for these studies, the need to improve detection efficiency remains. As such, the iFluX imaging spectrometer, with a large area X-ray panel based on a redesigned 2D-THCOBRA structure, is introduced.